Characterization of Electro-Optic Polarization Controllers for Implementation in Discrete-Variable Quantum Communications Transmitters - Martins, Luís Henrique Coutinho (2021)
Dissertação de Mestrado Integrado em Engenharia Física apresentada à Faculdade de Ciências e Tecnologia